2020
DOI: 10.3390/nu12061746
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking and Health in Ageing: A Global Scale Analysis of Older Individual Data through the Harmonised Dataset of ATHLOS

Abstract: We investigated the relation between alcohol drinking and healthy ageing by means of a validated health status metric, using individual data from the Ageing Trajectories of Health: Longitudinal Opportunities and Synergies (ATHLOS) project. For the purposes of this study, the ATHLOS harmonised dataset, which includes information from individuals aged 65+ in 38 countries, was analysed (n = 135,440). Alcohol drinking was reflected by means of three harmonised variables: alcohol drinking frequency, current and pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The positive correlation between the highest level of alcohol consumption and SRH in women was surprising. However, some evidence indicates that alcohol consumption may carry some health benefits for older women in terms of survival and quality of life, possibly mediated through a healthier drinking pattern than men and cardio-protective effects [ 16 , 49 51 ]. On the other hand, some studies have found that having a very good health status is a predictor of alcohol consumption, and not the other way around [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between the highest level of alcohol consumption and SRH in women was surprising. However, some evidence indicates that alcohol consumption may carry some health benefits for older women in terms of survival and quality of life, possibly mediated through a healthier drinking pattern than men and cardio-protective effects [ 16 , 49 51 ]. On the other hand, some studies have found that having a very good health status is a predictor of alcohol consumption, and not the other way around [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We selected the established factors that have been clearly identified in previous research as control variables for healthy aging (Appendix 2 in the Supplement), including: physical condition (chronic diseases, teeth) [ 2 4 , 34 , 35 , 38 , 40 ], SES (education, ACE, household income) [ 3 , 4 , 6 , 8 , 9 , 34 , 35 , 40 44 ], lifestyle habits (smoke, drink) [ 3 , 6 , 7 , 34 , 35 , 41 , 43 , 45 ], and demographic factors (geographical distribution, urban–rural distribution, age, gender, and marital status) [ 3 , 4 , 6 , 9 , 34 , 35 , 40 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol drinking status: Those who drink alcohol in the past 12 months from the time of data collection (Tyrovolas et al, 2020)…”
Section: Methodsmentioning
confidence: 99%
“…Length of hospital stay: Is the duration of a single episode of hospitalization which is calculated by subtracting the day of admission from the day of discharge (Tefera et al, 2020) Normal length of hospital stay: Hospital stays less than the 75 th percentile length of stay was used (Tefera et al, 2020) Prolonged length of hospital stay: Hospital stays greater than the 75 th percentile was used (Tefera et al, 2020) Smoking status: Who smoke in the past 3 months from the time of data collection (Jamal et al, 2018) Alcohol drinking status: Those who drink alcohol in the past 12 months from the time of data collection (Tyrovolas et al, 2020) Number of medication: Total number of medication taken by patients during hospital stay and classified as ≤2 and >2.…”
Section: Operational Definitionmentioning
confidence: 99%